2021
DOI: 10.1186/s12889-020-10151-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring capabilities in health and physical activity promotion: a systematic review

Abstract: Background The capability approach by Amartya Sen and Martha Nussbaum has gained increasing attention in the field of public health. As it combines individual, social and structural factors and shifts the focus of attention from the actual behavior towards available options for health behaviors that people can actually choose from, it may help advance our understanding of complex health issues. Objectives The aim of this article is to identify and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
0
2
0
1
Order By: Relevance
“…Senior:innen) erfolgen müssen. Bislang fehlen geeignete Messinstrumente zur standardisierten Erhebung bewegungsbezogener capabilities, wie eine systematische Übersichtsarbeit zeigt 20 . Auch fehlt bislang eine verständliche Formulierung von Fragebogenitems, um das komplexe Capability-Konstrukt adäquat zu erfassen.…”
Section: Introductionunclassified
“…Senior:innen) erfolgen müssen. Bislang fehlen geeignete Messinstrumente zur standardisierten Erhebung bewegungsbezogener capabilities, wie eine systematische Übersichtsarbeit zeigt 20 . Auch fehlt bislang eine verständliche Formulierung von Fragebogenitems, um das komplexe Capability-Konstrukt adäquat zu erfassen.…”
Section: Introductionunclassified
“…Fourteen newly developed instruments were identified, most of them with some evidence of psychometric properties, although further information about practical and theoretical characteristics of these measures is recommended to properly choose and apply them in both research and intervention. Another recent systematic review, concerning capabilities measurement in health, identified 11 questionnaires with good validity and reliability evidence (Till et al, 2021 ). These two literature reviews identified, so far, two capabilities instruments for mental health in intervention assessment (Helter et al, 2019 ; Till et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another recent systematic review, concerning capabilities measurement in health, identified 11 questionnaires with good validity and reliability evidence (Till et al, 2021 ). These two literature reviews identified, so far, two capabilities instruments for mental health in intervention assessment (Helter et al, 2019 ; Till et al, 2021 ). Both are multidimensional and self‐reported measures.…”
Section: Introductionmentioning
confidence: 99%